2015
DOI: 10.1002/star.201500016
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physicochemical, morphological, and structural properties between rice starch and rice flour modified by dry heat treatment

Abstract: The differential influence of dry heat treatment on pasting, thermal, morphological, and crystalline structural properties of glutinous rice starch (GRS) and glutinous rice flour (GRF) in a dry state for 0, 2, or 4 h at 130°C were studied. The results revealed that the viscosity and thermal stability of GRS and GRF increased after dry heat treatment. Peak viscosity of GRF rose nearly threefold from 1156 to 3145 cP. The number of disulphide bonds in GRF increased from 1.93 to 3.19 mmol/g, indicating the covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…However, MWT, due to much faster and uniform heat distribution as well as local superheating points and the loss of water during the process, can lead to other structure rearrangements reflecting in higher final crystallinity. Similar results were obtained by Qiu et al (2015) during dry heat treatment of rice flour which resulted in higher crystallinity of both rice flour and starch. These authors suggested that dry heat treatment may contribute to the formation of new crystallites or recrystallization and perfection of the small crystalline regions of the starch granule.…”
Section: A) Control B) 20%supporting
confidence: 83%
“…However, MWT, due to much faster and uniform heat distribution as well as local superheating points and the loss of water during the process, can lead to other structure rearrangements reflecting in higher final crystallinity. Similar results were obtained by Qiu et al (2015) during dry heat treatment of rice flour which resulted in higher crystallinity of both rice flour and starch. These authors suggested that dry heat treatment may contribute to the formation of new crystallites or recrystallization and perfection of the small crystalline regions of the starch granule.…”
Section: A) Control B) 20%supporting
confidence: 83%
“…The steaming and HTHP treatment increased the FV significantly up to 2688.5 and 1392 cP, respectively. In steaming process, the hydration of starch granule and vapour contributed to higher swelling power, which largely determined the viscosity of starch pastes (Qiu et al, 2015). Starch granule with high swelling power occupied large volume and arranged tightly (Huang & Lai, 2010).…”
Section: Pasting Properties Of Rye Flour With Different Heat Treatmentmentioning
confidence: 99%
“…Heat treatment has always been considered as a very effective way to achieve modifications in viscosity, rheological, processing or shelf-life properties of cereal flour and other milling products (Mariotti et al, 2006;Sharma et al, 2011). It is a promising method due to safety, simplicity, no environmental pollution and low cost (Qiu et al, 2015). Much research has been shown that heat treatment leads to increase in cereal flour viscosity (Sun et al, 2014a,b;Qiu et al, 2015) and dough elasticity (Qin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, DHT was utilized to change the paste viscosity and thermal properties. The change of physicochemical properties of dry heat treated starches were variously reported depending on starch source, amylose content, and difference with starch and flour . The utilization of hydrocolloids in DHT is also reported to modify morphological, rheological, and thermal properties of starch .…”
Section: Introductionmentioning
confidence: 99%